2006
DOI: 10.1161/01.atv.0000223144.65958.c3
|View full text |Cite
|
Sign up to set email alerts
|

Local Heat Shock Priming Promotes Recanalization of Thromboembolized Microvasculature by Upregulation of Plasminogen Activators

Abstract: Objective-Thromboembolization and subsequent microvascular perfusion failure is implicated in the pathology of a variety of diseases, including transient ischemic attack (TIA), stroke, and myocardial infarction, and also for the complications after interventional and microsurgical procedures in coronary heart disease and peripheral arterial occlusive disease. In vitro heat shock priming has been suggested to induce plasminogen activators, which are the major upregulators of the fibrinolytic system. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Uchiyama et al (30) described that adenovirus vectormediated overexpression of HSF1 gene reduced PAI-1 expression in arterial EC; however, their results were not verified using a gene knockdown approach or knockout animal model. The results of the present study support the report from Rücker et al (22). HSF1-mediated stress response is considered as an important chain reaction for a self-defense mechanism of the body.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Uchiyama et al (30) described that adenovirus vectormediated overexpression of HSF1 gene reduced PAI-1 expression in arterial EC; however, their results were not verified using a gene knockdown approach or knockout animal model. The results of the present study support the report from Rücker et al (22). HSF1-mediated stress response is considered as an important chain reaction for a self-defense mechanism of the body.…”
Section: Discussionsupporting
confidence: 92%
“…Results from previous studies on the relationship between PAI-1 and heat shock response or its mediators were controversial. Rücker et al (22) reported that local heat shock increased PAI-1 expression in arterioles from rat skeletal muscle. Uchiyama et al (30) described that adenovirus vectormediated overexpression of HSF1 gene reduced PAI-1 expression in arterial EC; however, their results were not verified using a gene knockdown approach or knockout animal model.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, these changes were related to mammary function and include 1) inhibited milk secretion by upregulating an endogenous milk enzymatic system (Rucker et al 2006, Silanikove et al 2009), 2) disrupted tight junction of mammary gland epithelial cells, increased casein degradation and decreased the protein synthesis (Stelwagen et al 1998, Silanikove et al 2000, Shamay et al 2003, and 3) disrupted cytoskeletal components and inhibited cell cycle of BMECs (Collier et al 2006, Du et al 2008. In this study, we also found that these genes, SERPINE, PLAU, and PLAUR, coding an endogenous milk enzymatic system were upregulated; some genes, such as RICTOR, PIK3 and ELF2, involving in mTOR signaling pathway of mediated protein synthesis were down-regulated (Table S1).…”
Section: Discussionmentioning
confidence: 84%
“…During certain stresses, including wounding or bleeding, the increased generation of PAI-1 from endothelial cells may play a protective role through maintaining fibrin clots or the integrity of the extracellular matrix. Rü cker et al (41) demonstrated that heat shock increased the expression of PAI-1 in vascular tissue of rat muscle. Uchiyama et al (42) reported that adenovirus vector-mediated overexpression of HSF1 gene reduced PAI-1 expression in cultured arterial endothelial cells, but the finding was not verified using any gene knockdown approach.…”
Section: Hsf1 In Glycated Ldl-induced Pai-1mentioning
confidence: 99%